Advances in astronomy:from big bang to the solar system - Advances in astronomy; Thompson J M T ed (World Scientific, 2005)
In this highly accessible book, leading scientists from around the world give a general overview of research advances in their subject areas within the field of Astronomy. They describe some of their own cutting-edge research and give their visions of the future. Re-written in a popular and well-illustrated style, the articles are mainly derived from scholarly and authoritative papers published in special issues of the Royal Society's Philosophical Transactions, the world's longest running scientific journal. Carefully selected by the journal's editor, topics include the Big Bang creation of the universe, the formation and evolution of the stars and galaxies, cold dark matter, explosive sun-spot events, and humankind's exploration of the solar system. The book conveys the excitement and enthusiasm of the authors for their work at the frontiers of astronomy. All are definitive reviews for
Keywords: Astronomy; Cosmology